Why da Vinci surgical robot is needed for the development of Polish medicine. First Polish experience with the surgical robot in the Regional Specialized Hospital in Wrocław, Research & Development Centre - Witkiewicz, Wojciech; Gawora, Patrycja (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Many experts expressed the view that traditional laparoscopic surgery has reached the end of its development. Further enhancement of the instrumentation and surgical technique refinement are no longer able to make substantial progress to classic laparoscopic surgery. Therefore, great hopes are placed in the dynamic development of surgical robots. Over the last decade, robotic surgery operations performed laparoscopically mastered, and then, with additional capabilities, displaced laparoscopy in some areas, and has become the reference procedure. Additionally, after taking into account the costs incurred by the hospital, social insurance and the patient during hospitalization and convalescence, robotic surgery turns out to be the cheaper method than conventional operations, or traditional laparoscopy.